THE STUDY OF MISSIONARY WORKS FOR KOREANS AND THE YAKUTS OF RUSSIAN ORTHODOX CHURCH IN THE MID 19TH CENTURY (1853-68) - Jo, Lee Byong (Farabi Journal of Social Sciences, 2019)
Abstract. The purpose of this study is to understand missionary worksfor aborigines, including Koreans, in Siberia and Far east regions by the bishopInnokenti Veniaminov(И.Вениаминов, 1797-1879) in the mid 19th century, inthe period of ‘Yakutsk and Blagoveshchensk Orthodox Metropolis(1853-68)’. Eventually, the study is to identify characteristics of missionary works by bishop Veniaminov for immigrants in these regions.Through this study, following conclusions were drawn.First, in terms of the external aspect, missionary works by bishop Veniaminov are also not free from the other missions with national-political nature. However, even though the format of missionary workswas national-political, in contents of his missions,an immense number of non national-political missions had been done. The first basis of this opinion was the purity and humanity of the bishop Veniaminov, which were shown in the process of missionary works and missions based on dedication and indigenization(translation of the Bible, the Gospels, a catechism and education of orthodoxy and propagation in immigrants’ languages). Secondbasis was the resourcing systemin missionary works.That is, besides financial aid from The Holy Governmental Synod(Central), in no small number of cases regional synod(regional) or church and diocese had replenished themselves(by selling candles) , and in some cases even donations from parishioners had been invested.